Pelatihan dan Pendampingan Pengelolaan Aset Wakaf - Wita Ramadhanti; Triani Arofah; Ratu Ayu Sri Wulandari; Oman Rusmana; Adi Indrayanto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This community service program aims to enhance the capacity of nazhir in managing waqf assets through structured training and mentoring. Many waqf managers in Indonesia still face challenges related to administrative governance, assets mapping, reporting, and the development of productive waqf business model. The program was implemented through workshop, interactive discussion, and on-site mentoring focusing on sharia compliance, financial recording, documentation, and strategic planning for productive waqf. The results indicate significant improvements in nazhir competencies, particularly in asset documentation and the preparation of simple management plans for waqf development. This program contributes to strengthening waqf governance and optimizing the economic and social benefits of waqf assets for the community.